Prevalence and risk factors for outer retinal layer damage after macula-off retinal detachment. Issue 5 (28th August 2019) - Malosse, Laure; Rousseau, Hélène; Baumann, Cédric; Angioi, Karine; Leroy, Bertrand; Sennlaub, Florian; Berrod, Jean-Paul; Conart, Jean-Baptiste
Abstract : Purpose: To report the prevalence of outer retinal layer (ORL) damage after macula-off rhegmatogenous retinal detachment (RRD) surgery and to determine its associated preoperative risk factors. Methods: 253 eyes successfully operated for macula-off RRD were included in the study. The integrity of the external limiting membrane (ELM), ellipsoid zone (EZ) and cone interdigitation zone (CIZ) of the photoreceptors was assessed at 1 month and 6 months using spectral-domain optical coherence tomography. Risk factors were analysed using univariate and multivariate logistic regression. The correlation between ORL integrity and visual outcomes was also evaluated. Results: CIZ, EZ and ELM defects were found in, respectively, 198 (93.4%) eyes, 100 (47.2%) eyes, 64 (30.2%) eyes at 1 month and in 160 (63.2%) eyes, 44 (17.4%) eyes and 18 (7.1%) eyes at 6 months. In multivariate analysis, duration of macular detachment was the only factor associated with ORL damage at 6 months (p=0.007). Best-corrected visual acuity significantly improved from 0.5±0.3 at 1 month to 0.3±0.3 logarithm of minimal angle of resolution at 6 months (p<0.001) and was strongly correlated with the number of affected bands (p<0.001). Conclusion: Prevalence of outer retinal band defects substantially decreased through the study period, confirming the ability of photoreceptors to recover over time. However, shorter interval to surgery and better visual outcomes were significantly associated with fewer defects within the ORL at 6 months. These findings suggest that earlier surgery may limit RRD-associated photoreceptor degeneration and improve the patient's visual prognosis.